Evaluation of recurrent glioma and Alzheimer’s disease using novel multimodal brain image processing and analysis - Leatherday, Christopher (Curtin University, 2016)
Novel analysis techniques were applied to two different sets of multi-modality brain images. Localised metabolic rate within the hippocampus was assessed for its ability to differentiate between groups of healthy, mildly cognitively impaired, and Alzheimer’s disease brains, and an investigation of its potential clinical diagnostic utility was conducted. Relative uptake and retention of two PET tracers (11Carbon Methionine and 18Fluoro Thymidine) in a post-treatment glioma patient cohort was utilized to perform survival prediction analysis.